Effective Multimodal Therapy for Chemically Aggravated Androgenetic Alopecia: A Case Report using PRP and Mesotherapy - Andrade, Poliana Laís Zanetti; Tomachevski, Fernanda Roberta Casagrande; Murakami, Aureanna Nairne Negrão; Zinco, Andre Gaspar; Murakami, Fábio Seigi (Brazilian Journal of Case Reports, 2025)
Androgenetic alopecia (AGA) is a common condition characterized by progressive hair loss, closely associated with androgen hormone activity and genetic predisposition. Although platelet-rich plasma (PRP) therapy has gained attention for its regenerative potential and ability to stimulate follicular activity, the synergistic effect of combining PRP with mesotherapy remains unexplored. This case report presents a successful protocol involving a male patient with advanced AGA whose condition was further aggravated by chemical damage from a bleaching procedure. The therapeutic protocol included intradermal injections of PRP in combination with customized blends of active ingredients by mesotherapy, administered in multiple sessions. Quantitative photographic analysis revealed a visual increase in hair density, along with notable improvements in hair thickness and scalp health. The patient expressed great satisfaction with both the aesthetic results and scalp comfort. These results demonstrate the potential of an integrative PRP-mesotherapy approach as safe and effective treatment for patients with complex androgenetic alopecia.